INVESTIGATING CASH FLOW VOLATILITY AND CASH HOLDINGS ACROSS ACCOUNTING REGIMES - Putu Putri Prawitasari (Universitas Sarjanawiyata Tamansiswa, 2025)
This research investigates the relationship between cash flow volatility and corporate cash holdings across different accounting regimes. Utilizing a qualitative approach and theoretical models based on information asymmetry, the study explores how accounting standards and financial reporting requirements influence corporate decisions on cash reserves. Data from the Scopus database is used to compare cash management practices between companies adhering to International Financial Reporting Standards (IFRS) and those following Generally Accepted Accounting Principles (GAAP). The findings reveal that companies operating under IFRS tend to maintain higher cash levels, indicating that the greater transparency and disclosure requirements of IFRS lead to more cautious liquidity management. This highlights the significant impact of regulatory frameworks on corporate behavior concerning cash reserves. These insights are crucial for policymakers, corporate decision-makers, and investors who aim to understand the drivers of cash holdings and their effects on firm performance and financial stability. The study emphasizes the role of accounting standards in shaping corporate financial strategies and offers a novel perspective by linking cash management practices to different accounting regimes, providing new insights into the effects of financial reporting standards on corporate liquidity.